Color Doppler Imaging and Glaucoma: Comparison of Doppler Waveform of Retrobulbar Vessels between a Glaucomatous Patient and a Healthy Subject - Verticchio Vercellin, Alice Chandra; Lombardo, Sara; Cutolo, Carlo Alberto; Tinelli, Carmine; Milano, Giovanni (International Journal of Innovative Research in Medical Science, 2016)
Ocular blood flow abnormalities are believed to play an important role in the pathogenesis of primary open angle glaucoma (POAG). For this reason the Colour Doppler Imaging (CDI) evaluation of the retrobulbar vessels is used for research purposes to investigate the degree of these abnormalities and their role in the pathogenesis of PAOG. The most widely measured variables are peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistivity index (RI) of the ophthalmic artery, central retinal artery, and short posterior ciliary arteries. According to a recent study that has found statistically significant differences in two variables measured in the ophthalmic artery, the early systolic acceleration (ESA) and the ratio between the mean velocities of the systolic and diastolic components (Sm/Dm), we present the CDI evaluation of a case of normal tension glaucoma (NTG) compared to a healthy subject. The values obtained are in agreement with the literature and all the measured velocities, except for the PSV and the RIs in the ophthalmic artery that were respectively reduced and increased as compared to the healthy volunteer. Moreover, ESA is reduced and Sm/Dm increased. Further studies are needed to evaluate the degree of the pathological alterations and their role in the progression of the optic nerve injury.